Making Space in Reflective Practices as an Emotional Pedagogy in a Children's Islamic Boarding School - Ika Wahyuningsih; Aji Pangestu (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
Strengthening emotion regulation has become an urgent priority in educational research and practice, particularly in learning environments that demand high levels of self-discipline, emotional control, and social adaptation in communal life. This study aims to explore the practice of making space as a pedagogical mechanism that mediates children's emotion regulation processes in the pesantren. The research was conducted at a children's Islamic Boarding School in Rembang, Central Java, Indonesia, involving 20 elementary school-age children and 4 caregivers. Data were collected through observation, interviews, and documentation study. The data were analyzed through four stages: data collection, condensation, display, and conclusion verification. The findings indicate that pesantren, responses to emotional triggers (ET) do not remain at the level of impulsive reactivity (IR) in the form of crying, anger, and harsh verbal expressions, but are mediated by the practice of making space (MS), manifested in momentary silence, withdrawal, writing, drawing, pausing play with peers, and engaging in free movement within reflective activities (RP) as part of emotion pedagogy (EP) embedded in children's daily lives, which is conceptualized as a space for the production of reflective-deliberative (RD) emotional responses. The study underscores that pesantrens may explicitly integrate emotion regulation into their pedagogical design through structured, programmed, and institutionally legitimized practices within boarding life.